KARTU POP UP TIGA DIMENSI UPAYA MENINGKATKAN PENGETAHUAN DAN PRAKTIK BERKONSTITUSI MELALUI PENDEKATAN GOOD NEWS CLASSMEETING - Didit Yoga Sudibyo (Program Studi Pendidikan Pancasila dan Kewarganegaraan FKIP Universitas Sebelas Maret, 2019)
Three Dimensional Pop Up Cards Efforts to Improve Constitutional Knowledge and Practices through the Good News Classmeeting, is the learning of PPKn in the counstitution field which emphasizes three components of PPKn learning, namely civic knowledge, civic skills and civic disposition. Learning with the help of three dimensional media Pop Up makes it interesting and makes it easy to learn articles in the UUD 1945 constitution. Learning with audio video media containing new news in constitutional practice brings students knowledge closer and will form students ready in constitutional practice in Indonesia Keywords: pop up cards, counstitution, good news classmeeting